solve question no 9 a
plz solve this step by step with explanation
Attachments:
![](https://hi-static.z-dn.net/files/d89/c1e8cc4ec6c6e90f09d751912359ead8.jpg)
Answers
Answered by
1
GIVEN
a. (2x+3y)^2=(2x+3y)^2+24xy
= (2x+3y)^2-(2x+3y)^2=24xy
=4x^2+9y^2+12xy-4x^2-9y^2+12xy
=24xy
proved .
b. (4a+7b)^2-112ab=(4a-7b)^2
=(4a+7b)^2-(4a-7b)^2=112ab
=16a^2+49b^2+56ab-16a^2-49b^2+56ab
=112ab
proved.
c.(3p+q)^2-(3p-q)^2=12pq
=9p^2+q^2+6pq-9p^2-q^2+6pq
=12pq.
proved .
This MAY HELP you
MARK as BRAINLIST answer
Similar questions